Chemical and anatomical changes in Liquidambar styraciflua L. xylem after long term exposure to elevated CO2. (March 2015) - Kim, Keonhee; Labbé, Nicole; Warren, Jeffrey M.; Elder, Thomas; Rials, Timothy G.
Abstract: The anatomical and chemical characteristics of sweetgum were studied after 11 years of elevated CO2 (544 ppm, ambient at 391 ppm) exposure. Anatomically, branch xylem cells were larger for elevated CO2 trees, and the cell wall thickness was thinner. Chemically, elevated CO2 exposure did not impact the structural components of the stem wood, but non-structural components were significantly affected. Principal component analysis (PCA) was employed to detect differences between the CO2 treatments by considering numerous structural and chemical variables, as well as tree size, and data from previously published sources (i.e., root biomass, production and turnover). The PCA results indicated a clear separation between trees exposed to ambient and elevated CO2 conditions. Correlation loadings plots of the PCA revealed that stem structural components, ash, Ca, Mg, total phenolics, root biomass, production and turnover were the major responses that contribute to the separation between the elevated and ambient CO2 treated trees. Highlights: First study of wood properties after 11 years of higher level of CO2 treatment. Elevated CO2 exposure does not impact structural components of wood. Total phenolics content and some inorganics were significantly affected. Branch xylem cells were larger under elevated CO2 . Cell wall thickness was thinner under elevated CO2 . Abstract : Elevated CO2 in atmosphere did not impact the structural components yet altered some of non-structural components and anatomical properties after 11 years of exposure on sweetgum.